Literacy Learning Innovations in Elementary Schools - Atikah Mumpuni; Ragil Dian Purnama Putri; Haryanto Haryanto (UM Purwokerto Press, 2023)
Literacy skills are needed to face the challenges of the 21st century. Therefore, it is necessary to make innovations that support literacy learning in elementary schools. The writing method used is a literature review. In this article, there are five articles analyzed to determine the innovation of literacy learning in elementary schools. Innovation in literacy learning in elementary schools can be done in terms of facilities and infrastructure, forms of activities, and content or content. The results of the analysis conducted show that literacy learning innovations in terms of facilities and infrastructure can be done with an interesting literacy corner and media use. Innovation in literacy learning in terms of the form of activities can be done by integrating literacy learning with literature and technology. Meanwhile, literacy learning innovation in terms of content or content can be done with food security literacy.